বাংলাদেশের অর্থনীতি - খান, মোঃ শামসুল কবীর; খানম, দৌলতুন নাহার (ঢাকা : বাংলা একাডেমী, 1996)
On the economic policies of Bangladesh.
Includes bibliographical references (p. 322-325).
In Bengali.
Keywords: Bangladesh -- Economic policy